The Development of Spatial Memory Analyzed by Means of Ecological Walking Task - Sorrentino, Pierpaolo; Lardone, Anna; Pesoli, Matteo; Liparoti, Marianna; Montuori, Simone; Curcio, Giuseppe; Sorrentino, Giuseppe; Mandolesi, Laura; Foti, Francesca (Frontiers in Psychology, 2019)
The present study is aimed at investigating the development of spatial memory in pre-school children aged 4-6 years using an ecological walking task with multiple rewards. The participants were to explore an open space in order to find nine rewards placed in buckets arranged in three spatial conﬁgurations: a Cross, a 3x3 Matrix and a Cluster composed of three groups of three buckets each. Clear age-related improvements were evident in all the parameters analysed. In fact, there was a general trend for younger children to display worse performances than the older ones. Moreover, males performed better than females in both the search efficiency and visiting all buckets. Additionally, the search efficiency proved to be a function of the difficulty of the configuration to be explored: the Matrix and Cluster configurations were easier to explore than the Cross configuration. Taken altogether, the present findings suggest that there is a general improvement in the spatial memory abilities in preschoolers, and that solving an open space task could be influenced by gender. Moreover, it can be proposed that both the procedural competences and the memory load requested to explore a specific environment are determined by its specific features.